Integrating Inclusive Design and Computing Education - Oleson, Alannah (My University, 2024)
To realize more equitable technology futures, it is not enough to simply adapt technology to be more inclusive after it is created. We will also need to equip technology creators with the skills they need to critically reflect upon bias and exclusion during the technology design process. The question of how to best to impart actionable inclusive design skills to today's computing students---tomorrow's technology creators---remains open. Computing interfaces are an illustrative site of inquiry for demonstrating the concrete impacts of design bias. Interfaces constrain interactions with technology, and by extension, who gets to benefit from technological access and who is excluded. Because technology carries perceptions of objectivity, it can be difficult for students to grasp how subjective design decisions might impact usability. I argue that enabling students to critically reflect upon the ways their design decisions impact users is a key aspect of developing inclusive computing interface design competence. My work makes four contributions through a series of qualitative and mixed-method studies. First, I contribute a dual-type model of design activity present in computing education contexts, highlighting the need for further investigation into design decision-making skills that help computing students understand the societal impacts of technology. Next, I contribute a set of student learning challenges that arise in introductory interface design courses which may prevent computing students from developing the skills they need to design inclusive technology. Then, I contribute a pedagogical technique that uses a novel strategy called assumption elicitation to help computing students learn to recognize and respond to computing interface design bias, as well as a case study evaluation of its efficacy and considerations for its use in post-secondary design learning contexts. Finally, through an Action Research study of this technique’s integration into post-secondary computing courses, I contribute pedagogical content knowledge for teaching inclusive interface design in computing courses, including descriptions of how instructors leveraged the technique to inspire critical reflection, hopefulness, and inclusive design agency in students. These contributions provide foundations for future work in the nascent subdiscipline of critical human-computer interaction (HCI) education research.
Thesis (Ph.D.)--University of Washington, 2023
Keywords: computing education; computing interface design; HCI education; human-computer interaction; inclusive design; pedagogical content knowledge; Information science; Computer science; Education; Information science